Maintenance of Regional Languages and Traditions Through the Preservation of The Togal Manika Makean Tribe of North Maluku - Alkadri Ajwan; Anwar Nada; Yuanyuan Wang; Guijiao Zou (Lingeduca: Journal of Language and Education Studies, 2023)
Language maintenance need to be done for the sake of non-existant languages. The extinction of language influences of local wisdom and make disappearance of the nation's assets. One way can be done is to preserve togal manika: a combination of music, dance, and song. This art comes from the island of Makean with the terms Makean Luar and Makean Dalam in North Maluku. This study explain (1) Diglosi that occurs in the Island of Makean, North Maluku, and explain (2) efforts to preserve the language of togal manika. Data collection using observation and interview. The results of the study found that (1) diglossia was occurred in Low Language in the familial sphere kinship, neighborhood, and friendship. In Higher Language, diglosi was occured in all domains: education, government, religion. Efforts to preserve the language of the Togal Manika.